LANGUAGE, POLARIZATION, AND THE EXPRESSION OF POLITICAL IDENTITY ON SOCIAL MEDIA: A LITERATURE REVIEW FROM A DIGITAL SOCIOLOGY PERSPECTIVE: BAHASA, POLARISASI, DAN EKSPRESI IDENTITAS POLITIK DI MEDIA SOSIAL: KAJIAN LITERATUR PERSPEKTIF SOSIOLOGI DIGITAL - Oman Sukmana; Anshar; Ilham Syah; Radinal Muhdar (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to examine the relationship between language, political polarization, and political identity expression in social media through a digital sociology approach. Using a systematic literature review method, this study analyzes various relevant scientific works in the last ten years. The main focus is directed at how language is used as a tool of political expression and how such linguistic practices shape individual and collective identities in the digital space. Data was obtained from journal articles, books, research reports, and conference proceedings obtained through academic databases such as Scopus, Web of Science, Google Scholar, and JSTOR. The results of the analysis show that linguistic practices on social media—such as the use of hashtags, ideological diction, and visual symbols such as memes and emojis—play a major role in strengthening political identity and deepening polarization. Social media also creates echo chambers and filter bubbles that hinder dialogue across ideologies. The approach of digital sociology allows for a deeper understanding of how power, symbols, and discourse are intertwined in the formation of public opinion in the digital age. In conclusion, language in social media is not just a means of communication, but also a political means that shape affiliations, conflicts, and social structures. This study recommends the need to strengthen digital literacy and communication ethics in building a healthy and inclusive digital public space.